A Normal Appearing Duodenal Papilla in Familial Polyposis Need to be Biopsied: A Case Report - Franzjosef Schweiger; Jasim Radhi; Roger M Roberge (Canadian Journal of Gastroenterology)
The upper gastrointestinal tract is the most common site of extracolonic neoplasms in patients with familial polyposis coli. The majority of these patients develops adenomas in the duodenal periampullary area, some of which progress to adenocarcinoma. Early diagnosis and long term endoscopic surveillance are widely recommended to prevent the development of invasive cancer by early treatment of these tumours. The authors report the case of an asymptomatic 50-year-old man with familial polyposis coli in whom an adenocarcinoma of the papilla was diagnosed by random biopsy in the presence of negative radiographic and endoscopic studies. This case emphasizes the importance of regular screening and endoscopic biopsies of the major duodenal papilla and periampullary region in polyposis patients.